Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1063/1.5018151
|View full text |Cite
|
Sign up to set email alerts
|

Dual origin of room temperature sub-terahertz photoresponse in graphene field effect transistors

Abstract: Graphene is considered as a promising platform for detectors of high-frequency radiation up to the terahertz (THz) range due to graphene ′ s superior electron mobility. Previously it has been shown that graphene field effect transistors (FETs) exhibit room temperature broadband photoresponse to incoming THz radiation thanks to the thermoelectric and/or plasma wave rectification. Both effects exhibit similar functional dependences on the gate voltage and therefore it was found to be difficult to disentangle the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 35 publications
10
105
1
2
Order By: Relevance
“…The low thickness of the heterostructures (<45 nm) and of the edge-contacts (∼45 nm) allows us to use a thinner oxide (70 nm) as encapsulating layer before g T deposition ( Figure 1C and D), thus increasing the effective gate-tochannel capacitance per unit area: C g ∼ 100 nF cm −2 for both samples. This parameter is important for THz FET detectors [25], since the responsivity (R v ), a figure of merit defined as the ratio between photovoltage (Δu) and impinging optical power, is typically proportional to the sensitivity of the FET conductance to changes in the gate voltage (V g ) [25].…”
Section: Resultsmentioning
confidence: 99%
“…The low thickness of the heterostructures (<45 nm) and of the edge-contacts (∼45 nm) allows us to use a thinner oxide (70 nm) as encapsulating layer before g T deposition ( Figure 1C and D), thus increasing the effective gate-tochannel capacitance per unit area: C g ∼ 100 nF cm −2 for both samples. This parameter is important for THz FET detectors [25], since the responsivity (R v ), a figure of merit defined as the ratio between photovoltage (Δu) and impinging optical power, is typically proportional to the sensitivity of the FET conductance to changes in the gate voltage (V g ) [25].…”
Section: Resultsmentioning
confidence: 99%
“…2a). This behaviour is common for this type of devices and is related to additional rectification by p-n junctions at the boundaries between the p-doped graphene channel and the n-doped contact regions 24,31,32 .…”
Section: Broadband Operationmentioning
confidence: 94%
“…The responsivity of the device to different frequencies radiation at liquid helium temperature Thus, we showed that FET device with carbon nanotube film as a transport channel detect THz radiation in all temperature ranges. Previously CVD graphene device in the Dyakonov-Shur configuration was shown to have 1V/W responsivity [5] and graphene encapsulated between two slabs of hexagonal boron nitride 20V/W [6]. In comparison with this CNT device shows responsivity up to 100V/W to radiation of THz frequency range.…”
Section: Fig 2 Transistor Characteristic Of the Tested Sample Measumentioning
confidence: 82%